EMOTION DETECTION USING RELATIVE BIN FREQUENCY COEFFICIENTS, RELATIVE SUB-IMAGE BASED AND BIMODAL INFORMATION - KUDJRI, KRISHNA MOHAN (2015)
When human interacts with the computer, the estimation of basic emotions (angry, sad, happy, surprise, fear and disgust) of human through facial expressions during speech process is needed to be investigated. Although, some studies have been conducted to estimate the basic emotions through facial expressions during speech process in the past, a thorough understanding of the science of the process is yet to be arrived at.